Plantas de cobertura no vazio outonal e sua influência na produtividade da cultura do trigo - Fornari, Ezequiel Zibetti (2023)
In the state of Rio Grande do Sul (RS), agriculture is mainly based on soybeans or corn in the summer, and wheat in the winter. Between the harvest of the summer crop and the sowing of the winter crop, there is a window of 70 to 120 days in which the soil is unprotected. Therefore, cover crops appear as an option to minimize the damage caused by autumn fallow. Thus, the objective of this work was to evaluate the influence of cover crops on wheat crop productivity, as well as the biomass production capacity and nutrient cycling in the autumn void of RS. The work was carried out in the municipality of Cruz Alta-RS, in a commercial area, with soil classified as a typical Dystrophic Red Oxisol. The experimental area had 13.2 hectares, where 33 cover crop systems were cultivated after the corn crop, which preceded the wheat crop. Approximately 90 days after sowing, these cover crops were sampled to determine the potential for fresh and dry biomass production, nutrient content and accumulation (N; P; K; Ca; Mg; S, and C). and C/N, C/P and C/S relations. Afterwards, wheat was sown with the cultivar TBIO Audaz. The harvest was carried out mechanized, generating spatialized data on individual wheat yields for each cover crop system. Once data collection was completed, they were grouped into four groups (legumes, grasses, other species and intercropped systems). For each group, statistical analysis was performed using the Student's t test for independent samples with a 5% probability of error, in order to discriminate the best treatments within each group. Cover crops showed great variability in biomass production and nutritional composition, even in species from the same family. The C/N ratio varied from 10 to 31 for the single cultivation of common vetch and the intercropping of buckwheat and millet respectively. Most cover crops have a C/P ratio that provides P mineralization, with values below 200. On the other hand, the C/S ratio of most plant residues is above 200, reducing the rate of P mineralization. sulfur. Among the legumes, crotalaria juncea presented the highest dry biomass productivity with 9,317 kg ha-1. In the dry biomass productivity of grasses, there is a predominance of species from tropical climates in relation to those from temperate climates. In terms of nutrient accumulation, crotalaria juncea stands out with cycling of 219 and 156 kg ha-1 of N and K, respectively, and giant crow's foot grass with accumulations of 139 and 235 kg ha-1 of N and K, respectively. The lowest wheat productivity was found under millet residues with 3178 kg ha-1, with the highest productivity found under pig bean and gray velvet residues with 4949 and 4394 kg ha-1, respectively.